PH Effects on solubility, zeta potential, and correlation between antibacterial activity and molecular weight of chitosan. (10th December 2015) - Chang, Shun-Hsien; Lin, Hong-Ting Victor; Wu, Guan-James; Tsai, Guo Jane
Highlights: Six chitosans with molecular weights ranging from 3.3 to 300 kDa were prepared. Combined effects of chitosan MW, temperature, pH on bacterial growth were studied. The pH effects on water solubility and zeta potential of chitosans were examined. Positive correlation between chitosan ZP and antibacterial activity was obtained. Abstract: Six chitosans with molecular weights (MWs) of 300, 156, 72.1, 29.2, 7.1, and 3.3 kDa were prepared by cellulase degradation of chitosan (300 kDa) and ultrafiltration techniques. We examined the correlation between activity against Escherichia coli and Staphylococcus aureus and chitosan MW, and provided the underlying explanation. In acidic pH conditions, the chitosan activity increased with increasing MW, irrespective of the temperature and bacteria tested. However, at neutral pH, chitosan activity increased as the MW decreased, and little activity was observed for chitosans with MW >29.2 kDa. At pH 5.0 and 6.0, chitosans exhibited good water solubility and zeta potential (ZP) decreased with the MW, whereas the solubility and ZP of the chitosans decreased with increasing MW at pH 7.0. Particularly, low solubility and negative ZP values were determined for chitosans with MW >29.2 kDa, which may explain the loss of their antibacterial activity at pH 7.0.